Investigation of the apparent kinetics of air and oxy-fuel biomass combustion in a spouted fluidised-bed reactor - Yan, Yongliang; Clough, Peter T.; Anthony, Edward J. (Elsevier, 2019)
A bench-scale spouted fluidised-bed reactor was used to investigate the combustion kinetics of pulverised woody biomass under air and oxy-fuel atmospheres. Bed temperatures were in the range of 923-1073 K and O2 concentrations were varied from 20-35 vol%. The activation energies and apparent orders of reaction were calculated for air and oxy-fuel combustion by means of an nth order Arrhenius equation approach. Results indicated that the apparent order of reaction for both air and oxy-fuel combustion was approximately zero. The activation energies were calculated assuming a zero-order reaction mechanism and were averaged over all oxygen concentrations for air and oxy-fuel combustion and found to be 18.95 kJ/mol and 26.93 kJ/mol, respectively. The rate of combustion under oxy-fuel conditions was, on average, 37.5% higher compared to air combustion. The shrinking core model with a reaction-controlled step was found to accurately represent the biomass combustion reactions under both air and oxy-fuel conditions.
Keywords: Combustion; Kinetics; Biomass; Oxy-fuel; Spouted fluidized bed; Carbon capture and storage